THEORY OF MORAL AND LEGAL EDUCATION S.Y. HESSEN: THE MOTIVATION OF HIS MODERN REQUEST - Lobanova, A.S. (Pedagogy of Higher and Secondary Education, 2010)
Essence of theory of moral and legal education of prominent teacher-philosopher S.I. Gessens is analysed in the article. Grounded necessity of modern query of this theory for the improvement of the system of primary education. Attention is accented on expedience of rational combination in education and formation of clever freedom and discipline as forms of social control.